2015
DOI: 10.7567/jjap.55.01ae07
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical analysis of single phase CuInS2 nanocrystals for solar cell applications

Abstract: Nanostructured phase pure CuInS2 particles have been successfully synthesized by solid state melt growth method. The crystallographic structure, morphological, chemical composition and optical properties of synthesized sample have been characterized by various analytical techniques, includes X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive X-ray (EDAX), UV–vis–NIR diffuse reflectance spectroscopy and photoluminescence spectroscopy. From the XRD spectra chalcopyrite structure of Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Numerous papers have also been devoted to the investigation of the physical and chemical properties of CuInS 2 . However, when it comes to CuInS 2 NCs, or, in general, low-dimensional CuInS 2 of either zinc blende (cubic) or wurtzite (hexagonal) structural type, the number of studies becomes rather limited. , , According to the literature data, these films have generally been prepared by conventional growth methods such as sputtering, evaporation, and chemical vapor deposition, while synthetic routes to nanocrystals have often been realized under harsh conditions (such as high vacuum and high temperature). This increases the cost of synthesis processes, and at the same time, they are hardly scaled up to produce large amounts of the material on an industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous papers have also been devoted to the investigation of the physical and chemical properties of CuInS 2 . However, when it comes to CuInS 2 NCs, or, in general, low-dimensional CuInS 2 of either zinc blende (cubic) or wurtzite (hexagonal) structural type, the number of studies becomes rather limited. , , According to the literature data, these films have generally been prepared by conventional growth methods such as sputtering, evaporation, and chemical vapor deposition, while synthetic routes to nanocrystals have often been realized under harsh conditions (such as high vacuum and high temperature). This increases the cost of synthesis processes, and at the same time, they are hardly scaled up to produce large amounts of the material on an industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The average size (D) of the CuInS 2 nanocrystals is calculated to be ∼3.2 nm by the Scherrer formula D = Kλ(B cos θ) −1 , where K is a constant (0.9), λ is the X-ray wavelength (1.54056 Å), B is the full width half-maximum (in radians), and θ is the Bragg angle of the (112) peak. 23,24 We also observed the TiO 2 /CdS/CuInS 2 films with the annealing temperature (T a ) of 250 and 300 °C. As shown in Figure S2, an increase in T a imposes a slight effect on the resulting CuInS 2 nanoparticle size but leads to the intensified XRD peaks of CuInS 2 suggesting a higher T a for a higher CuInS 2 crystallinity; however, Raman data showed that a binary chalcogenide (Cu x S y ) impurity appeared at T a = 300 °C.…”
Section: Resultsmentioning
confidence: 79%
“…The broad absorption extending from the ultraviolet to near-infrared regions indicates actually a broad size distribution of CuInS 2 nanoparticles in the CuInS 2 layer, including quantum dots with a size smaller than Bohr exciton radius (∼4.1 nm) 11,22,23 and nanoparticles with a diameter larger than 8 nm. 15,21,24,27 Noticeably, the annealing temperature T a almost imposed no remarkable influence on the CuInS 2 film absorption property, and the very comparable absorbance was observed in the 200 nm-thick CuInS 2 layers prepared at T a = 250−300 °C (Figure S5a).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations